Sejarah Perkembangan Filologi di Timur Tengah dan Pengaruhnya dalam Penyebaran Islam - Riyan Haqi Khoerul Anwar; Dedi Supriyadi (Definisi: Jurnal Agama dan Sosial Humaniora, 2022)
This paper aims to explain the development of philology in the Middle East. This study is important because the development of philology is related to other sciences. The research method used is a literature review (library research). This paper reveals that the development of philological studies in the Middle East cannot be separated from the influence of ancient Greek civilization. Various Greek cultural texts became guidelines in various fields of scientific discipline, especially philosophy and exact sciences. Philological activity in the Middle East began in the 4th century and then developed in the 5th century with many philologists from Edesse moving to the Persian region. The subsequent development of this Greek study was adopted by the Abbasid caliphate until it continued to decline in the next generation. The impact of the existence of this philology is great, especially in the spread of Islam and Arabic, especially to correct an error information related to the manuscript or text.